A1.72 Baricitinib, an oral janus kinase inhibitor, in the treatment of rheumatoid arthritis: safety and efficacy in an open-label, long-term extension study1. (31st January 2014) - Taylor, Peter; Genovese, Mark; Keystone, Ed; Schlichting, Douglas; Beattie, Scott; Macias, William
Abstract : Background: Baricitinib (formerly LY3009104/INCB028050) is a novel, oral inhibitor of JAK1 and JAK2 in the JAK-STAT signalling pathway being investigated as a treatment for rheumatoid arthritis (RA). Objectives: To report 52 week safety and efficacy findings of an open label extension of the phase 2b study. Methods: Patients (Pts) were initially randomised to placebo (PBO) or 1of 4 once-daily (QD) baricitinib doses (1, 2, 4, or 8 mg) for 12 wks. Pts assigned to 2 mg, 4 mg or 8 mg continued assigned treatment and pts assigned to placebo or 1 mg were reassigned to 4 mg QD or 2 mg BID for an additional 12 weeks of blinded treatment. In the open label portion of the study, patients in 8 mg group continued to receive 8 mg QD and all other patients received 4 mg QD. Doses could be escalated to 8 mg QD at 28 or 32 weeks at the investigator's discretion when >6 tender and swollen joints were present. Analyses reported here include data through 52 weeks for patients treated in the open-label extension (non-responder imputation used for discontinued patients). Results: Of the 212 pts eligible to participate, 201(95%) pts entered the open label extension, 184 patients completed 52 weeks of treatment, 15 pts discontinued, and 2 pts had not yet completed 52 weeks. Among pts who remained on 4 mg (n = 108), TEAEs occurred in 57 (53%), SAEs in 14 (13%), infections in 34 (31%) and serious infections in 4 (4%). Among pts who received 8 mg at any time (n = 93), TEAEs occurred in 59 (63%), SAEs in 8 (9%), infections in 37 (40%) and serious infections in 2 (2%). No opportunistic infections or TB cases were observed. There was one death due to myocardial infarction in the 8 mg group. Among all patients combined in the open label extension, the proportions of pts achieving ACR20, ACR50, ACR70, CDAI Remission, SDAI Remission, DAS28CRP ≤3.2, DAS28CRP <2.6, DAS28ESR ≤3.2, DAS28CRP <2.6 or the ACR/EULAR Boolean remission at the start of the open label extension (week 24) were similar or increased at week 52 (Table). Conclusions: Among pts completing 52 weeks of a phase 2b study, clinical improvements observed at week 24 were maintained or improved during the open label extension. Safety signals observed over the open label extension were consistent with previously reported results of baricitinib. Reference: 1.1. EULAR 2013, Ann Rheum Dis 2013;72 Supplement 3:65, Genovese et al.